Analysis of the utilization of inspectorate audit report provincial and regency/city inspectorates by BPK representative of North Sulawesi Province - Haryanto , Ag. Dwi; Tinangon, Jantje J.; Walandouw, Stanley Kho (The Contrarian : Finance, Accounting, and Business Research, 2024)
This study aims to determine the implementation of the use of the Provincial and Regency/City Inspectorate Audit Report (LHP) by the BPK Representative of North Sulawesi Province in the period of 2021 to 2023, obstacles and efforts to overcome obstacles. This research uses a qualitative method. Data collection with unstructured observations, in-depth interviews, and documentation. The results of the study show that the LHP of the Regional Inspectorate has not fully made an active contribution to the preparation of the program, implementation, and control of audit activities by the BPK Representative of North Sulawesi Province. The LHP of the Regional Inspectorate has contributed when the BPK Audit Team carried out the audit task. The BPK Audit Team is active in requesting the Regional Inspectorate's LHP and the Regional Inspectorate's Annual Supervision Work Program (PKPT) during the implementation of the audit task used in examining problems and recommendations along with not continuing the Regional Inspectorate LHP. The results of the BPK Audit Team's study are used in the preparation of the business risk matrix, fraud risk matrix, sample selection strategy and preparation of additional/alternative procedures if necessary. The obstacle to the use of the Regional Inspectorate LHP for BPK is the lack of understanding of the obligation of the Regional Inspectorate to actively submit its LHP to the BPK, the lack of timely receipt of the Regional Inspectorate LHP by the BPK Audit Team so that an in-depth evaluation cannot be carried out, the scope of the Regional Inspectorate LHP object is less relevant to the needs of the Audit Team. The efforts that have been made by BPK are that the BPK Audit Team has made a written request for the list of LHPs along with the LHP of the Regional Inspectorate and the Badiklat PKN BPK RI has opened opportunities to improve the competence of Regional Inspectorate inspectors with training for Regional Inspectorate inspectors.